Analysis on the survey of e-zakat system among zakat applicants of Universiti Teknologi MARA (UiTM) Johor / Khadijah Amira Abdul Rashid, Mahasin Saja@Mearaj and Ezril Hisham Mat Saat - Abdul Rashid, Khadijah Amira; Saja@Mearaj, Mahasin; Mat Saat, Ezril Hisham (UiTM Cawangan Johor, 2024)
Unit Zakat, Sedekah dan Wakaf (UZSW) is known as a zakat institution under Universiti Teknologi Mara (UiTM) Johor. There are various functions of this unit including managing zakat distribution fund according to the distribution management procedures that have been set. However, as the system is newly developed, it is certain that this system needs feedback from the users, especially from the zakat applicant. The purpose of this research is to study the effectiveness of the online zakat application system (e-ZAKAT) among zakat applicants consisting of UiTM Johor students. This research used quantitative method in the form of survey through Google Form application. The data were collected and analyzed using Statistical Packages of Social Science (SPSS). The results of the study showed that all the items had a high mean value. It means that most of the respondents chose agree and strongly agree that e-ZAKAT system is easier, beneficial and user-friendly.